2003
DOI: 10.1002/pd.650
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐gestation Down syndrome screening test and pregnancy outcome among unstimulated assisted‐conception pregnancies

Abstract: OD embryos are a unique clinical model for evaluating the uterine compartment and its contribution to mid-gestation serum marker secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 16 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, our study was limited in classification of fresh versus frozen transfer of embryos. Prior studies have shown that frozen embryo transfer results in elevated AFP and/or hCG levels (Shulman and Maymon, 2003;Hui et al, 2003), consistent with findings in our ED group. A large group with a number of EDs performed without freezing before embryo transfer would need to be studied to separate the effects of donation from the effects of frozen storage on serum marker levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our study was limited in classification of fresh versus frozen transfer of embryos. Prior studies have shown that frozen embryo transfer results in elevated AFP and/or hCG levels (Shulman and Maymon, 2003;Hui et al, 2003), consistent with findings in our ED group. A large group with a number of EDs performed without freezing before embryo transfer would need to be studied to separate the effects of donation from the effects of frozen storage on serum marker levels.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of IUI on Down syndrome screening markers have not been well studied, although it seems that the second-trimester marker patterns are similar to those in IVF pregnancies, with decreased AFP (Hsu et al, 1999) and uE3, and increased beta-hCG (Barkai et al, 1996), while the first-trimester markers are unaffected (Liao et al, 2001;Wojdemann et al, 2001). Pregnancies achieved with ED are reported to have increased AFP and hCG (Barkai et al, 1996;Maymon and Shulman, 2001;Hui et al, 2003;Shulman and Maymon, 2003), but the levels of other markers have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown such association with intrauterine growth retardation [1] , maternal hypertension [2,3] , fetal malformations, chromosomal aberrations [4] , and adverse perinatal outcome [5] . The poor outcome was reported in infertility patients [6] and during the first trimester [7] . The purpose of the current study was to analyze the characteristics of a group of pregnancies with extreme elevation of MShCG.…”
Section: Introductionmentioning
confidence: 99%